THE INFLUENCE OF ENTREPRENEURSHIP PRACTICE ON ENTREPRENEURIAL INTEREST OF GRADE XII STUDENTS AT SMK ISLAM AL AMIN CIKARANG UTARA - lya Komalasari; Eka Putri; Uza Sukmana (Cakrawala Pedagogik, 2025)
This study aims to analyze the influence of entrepreneurship practice on the entrepreneurial interest of grade XII students at SMK Islam Al Amin Cikarang Utara. The research population consisted of all grade XII students totaling 162 students, with a sample of 62 students determined using the Slovin formula. The research method employed a quantitative approach with data collection techniques through questionnaires. Data analysis used descriptive statistics, prerequisite analysis tests (linearity and normality tests), simple linear regression, partial statistical test (t-test), and coefficient of determination (R²). The research results show that entrepreneurship practice has a positive and significant influence on the entrepreneurial interest of grade XII students at SMK Islam Al Amin Cikarang Utara. This is evidenced by a significance value of 0.000 < 0.05, indicating that linearity is fulfilled. The normality test shows normal distribution for both variables with significance values of variable X at 0.084 > 0.05 and variable Y at 0.068 > 0.05. The simple linear regression equation Y = 30.897 + 0.469X indicates a positive influence. The t-test results obtained t_calculated value of 3.874 > t_table 2.003, thus H? is rejected and H? is accepted. The coefficient of determination (R²) of 0.200 indicates that entrepreneurship practice contributes 20% to entrepreneurial interest, while 80% is influenced by other factors. In conclusion, the better the entrepreneurship practice is implemented, the higher the students' entrepreneurial interest